KINERJA DINAS PENDIDIKAN KEPEMUDAAN DAN OLAHRAGA KOTA DENPASAR DALAM PENGAWASAN SISTEM ZONASI TAHUN 2018 - Novianti Abrahams, Corilin Aksamina; Yudartha, I Putu Dharmanu; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2019)
ABSTRACT Indonesian education has a system for implementing education aimed at increasing knowledge and being able to grow potential. then there is a fair distribution of the education system. This study aims to describe the performance of the Denpasar City Education and Sports Service in supervising the 2018 zoning system in zones 1 to 4 of secondary schools in the city of Denpasar. Using qualitative methods with techniques, data collection techniques, data analysis techniques and data presentation techniques. The theory is (1) productivity, (2) quality, (3) responsiveness, (4) responsibility, (5) accountability. Results, productivity of the Department of Youth and Sports Education is still considered lacking because it is not optimal, the responsibility of the Office of Education is also felt to be lacking. The quality of services provided by schools must also be considered where schools in this case must be more selective and open to the acceptance of new students. Keywords: Productivity, quality, responsiveness, responsibility.